Room rate parity vs. Rate fences in the context of price discrimination theory: the case of the Polish hospitality market - Biełuszko, Katarzyna; Marciszewska, Barbara (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2018)
Rate parity is still a very controversial issue, thus many researchers and industry professionals study it with respect to several aspects: whether it is beneficial for the hotel and/or for the customers. However, despite the necessity to respect rate parity, many hotels do not apply this requirement. Therefore, the authors have attempted to assess this phenomenon in the Polish hospitality market. The aim of the study was to determine the scope of applying rate parity by Polish hotels and using the price discrimination in a variety of direct and indirect channels of electronic distribution. The purpose was to state how the restriction to respect rate parity by the hotels affects the possibility of using price differentiation. The research material involved prices available on-line across various distribution channels. The research methods were based on a critical analysis of literature and on the observation of the prices on the websites of 311 hotels and e-intermediaries. The collected data were analyzed statistically by means of SPSS software. The relationships between the characteristics of the hotels (the category and belonging to a chain) and the variables were determined. The analysis indicates that the necessity of applying rate parity paradoxically often leads to using price differentiation and rate fences by the hotels. Among the hotels applying rate parity (i.e. the same standard room rate as in other distribution channels) as many as 61% of enterprises use rate fences (mainly non-physical – transaction features) in order to improve the competitiveness of their prices in relation to other distribution channels.
Argumenta Oeconomica, 2018, Nr 2 (41), s. 113-133
Keywords: room rate parity; price discrimination; rate fences; e-intermediaries; Polish hospitality market